NAMA KELUARGA DALAM BAHASA INGGRIS DAN BAHASA MOI (ANALISIS KONTRASTIF) - SURIPATTY, JULIANA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT This study is an attempt to describe and analyze the family names in English and the Moi language. In this research the writer uses Hickerson’s theory and McVetty’s concept. The aims of this research are to identify and classify and to find out the kinds and meaning of the family names in English and in Moi language and to contrast them, in order to find the similarities and the differences. There are two significant contributions from this study. Theoretically this study gives contributions to the language development especially in Moi language’s community. Practically it enriches the knowledge of students in learning language especially the kinds and meanings in terms of family names for Moi language. The results show that five types of the English family names have (1) patronymic family names, (2) family names referring to place of origin or locality, (3) family names refering to occupation, (4) family names referring to nickname as well as family names adopted from given name, and (5) family names referring to identity of its family; whereas Moi family names have (1) family names referring to place of origin or locality, (2) family names referring to occupation, (3) family names referring to nickname as well as adopted from given name, and (4) family names referring to identity of its family. Keywords : Family Names English and Moi Language, Contrastive Analysis